BATCHING PLANT OPTIMIZATION IN GEMPOL – PASURUAN – PROBOLINGGO ROAD AND BRIDGE PRESERVATION PROJECT - Kusuma, Indri Yunita; Purnomo, Fadjar; Rasidi, Nawir (Jurusan Teknik Sipil Politeknik Negeri Malang, 2023)
The Gempol – Pasuruan – Probolinggo Road and Bridge Preservation Project handles roads along 5 scopes of work, namely major rehabilitation, reconstruction, bridge rehabilitation, bridge periodicals and bridge replacement. Work that requires ready mix concrete is in the scope of major rehabilitation and bridge replacement. Making ready mix concrete requires heavy equipment such as batching plants and mixer trucks. In this case, optimization is carried out to minimize the cost of providing ready mix concrete. This optimization was carried out on STA KM Sby 96+600 to KM Sby 98+390 and KM Sby 102+300 to KM Sby 103+700 and Kademangan Bridge III and IV. The purpose of this optimization is to determine the number of ready mix concrete needs, the optimal number and batching plants, and the selection of the best ready mix concrete provider for this project. The data needed for this thesis work is the volume of work, shop drawings, project work schedules, and heavy equipment specifications. The transportation method is used to optimize the batching plant. The optimization result of the distribution of ready mix concrete is needed for ready mix at location 1 is 2,915 m3 from batching plant 1 (PT. Waskita Beton Precast); from batching plant 3 (PT. Merak Jaya Beton, Wonorejo) is 1,210 m3; from batching plant 4 (PT. Merak Jaya Beton, Porong) is 689 m3; at location 2 is 2,429 m3 from batching plant 2 (PT. Merak Jaya Beton, Paiton); from batching plant 3 is 872 m3; from batching plant 4 is 605 m3; at location 3 is 61 m3 from batching plant 1; from batching plant 3 is 7 m3; and at location 4 is 51 m3 of batching plant 2; from batching plant 3 is 8 m3. The optimal distribution cost of concrete distribution is Rp20,889,522,557.77,-.